On some finitely generated subsemigroups of S(X) (Journal of Humanitarian and Applied Sciences, 2020)
S(X) is the semigroup, under composition, of all continuous selfmaps of the topological space X. In this paper, we show for a number of spaces that S(X) contains a dense subsemigroup generated by two elements when S(X) given the compact-open topology.
Keywords: semigroup; clopen set; continuous selfmap; IN-absorbing space; compact-open topology